Highly Sensitive Temperature Sensing in Biological Region with Ratiometric Fluorescent Response - Yan Li; Han Yu; Hongjuan Li; Shiguo Sun; Ruijin Yu; Yongqian Xu (Molecules)
Poly(2-oxazoline) (POx), a typical thermoresponsive polymer with good biocompatibility, was conjugated with environment-sensitive tetraphenylenethene (TPE) and hydroxyphenylbenzoxazole (HBO) to achieve unique thermometer readings. Through phase transition induced by temperature, the thermometers can measure temperature in biologic range with ratiometric fluorescence response, ultrahigh sensitivity and good reversibility. Moreover, the thermometer can be used to measure the change in temperature with large fluorescence difference in living cells.